2018
DOI: 10.1177/0731684418760206
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of kenaf fiber and its composites: A review

Abstract: Nowadays, fiber-reinforced composites have gained attention due to their improved potential for replacing the conventional materials in various applications. Kenaf fiber has been widely used as reinforcement in composites over the past few years which is a most attractive alternative due to its rapid growth at different climatic conditions and ensuring low cost; kenaf fiber has gained some attention to replacing the glass fiber composite and making it purely an eco-friendly composite. However, for enhancing it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 48 publications
0
29
0
1
Order By: Relevance
“…1 Natural fibres, such as kenaf, bamboo, coir and sisal, have been investigated throughout the years as reinforcements of polymer matrices. [2][3][4][5][6][7][8] These have proven to be highly resistant materials, 9 and also offer health/ environmental benefits since they are non-carcinogenic and safe during processing and handling. 10 Research has been focussed on the study of the mechanical behaviour of composite materials reinforced with natural fibres due to their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…1 Natural fibres, such as kenaf, bamboo, coir and sisal, have been investigated throughout the years as reinforcements of polymer matrices. [2][3][4][5][6][7][8] These have proven to be highly resistant materials, 9 and also offer health/ environmental benefits since they are non-carcinogenic and safe during processing and handling. 10 Research has been focussed on the study of the mechanical behaviour of composite materials reinforced with natural fibres due to their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Natural fibers were emerged as realistic alternatives to produce polymer-based fiber composites because of their high abundance as most of them are agricultural crops [5]. These renewable fillers with a high specific strength have shown a great ability to improve the mechanical and thermal properties of polymeric supports due to their inherent properties [6][7][8]. Among all, WF is a lignocellulosic fiber which can be obtained from industrial processes as a waste product.…”
Section: Introductionmentioning
confidence: 99%
“…With the stem of kenaf used as a biomass material, the other parts are edible and rich in pharmacological ingredients, which is an added bonus when compared to other energy‐dedicated crops (Giwa Ibrahim et al., 2019). In addition, kenaf is less affected by climate and has a fast growth rate (~4 months), making the plant more robust than conventional biomass for mass production (Islam, 2019; Ramesh et al., 2018). This are the few studies that tested different cultivars from one crop, and even for the same crop, the SSF results were significantly different depending on the cultivars, and it was confirmed that such sugar content and acetate content greatly influence the fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…First, kenaf can grow up to 4–5 m tall and be harvested up to three times a year (Islam, 2019). Second, the plantation cost of kenaf is low since the plant can grow in a variety of climate conditions (Ramesh et al., 2018). The annual production yield of kenaf is 10.9–27.2 tons/ha (Kamaruddin & Othman, 2012), which is larger than any other lignocellulosic biomass including agricultural wastes and forestry residues (see Table 1).…”
Section: Introductionmentioning
confidence: 99%